Analysis of Production Budget Formulation Using the Least Squares Method at CV. Amirah Ramadhani Cemara, Makassar - Alda Hikmah Rhamadani Juyot Limpo; Idris Hariany; Samsinar Samsinar (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study investigates the application of the Least Squares method for production budget planning at CV. Amirah Ramadhani Cemara Kora, Makassar. Employing a quantitative descriptive approach, the research analyzes sales data from January to December 2024, beginning inventory data for January 2025, and 2024 production reports, substantiated by interview data. The findings indicate that the Least Squares method yields significantly more accurate and structured production forecasts compared to the company's previous conventional methods. Analysis using the trend equation Y = a + bX reveals a consistent upward trend from January to December 2025, thereby mitigating risks associated with overstocking or stockouts. The projected 2025 production budget estimates a total output of 6,808 short-sleeve shirts and 6,466 long-sleeve shirts. The total estimated production cost is IDR 749,205,900, comprising IDR 463,920,000 for raw materials, IDR 66,830,000 for direct labor, and IDR 218,455,900 for factory overhead. This approach enables the company to optimize raw material and labor allocation based on predictive trends, effectively preventing production inefficiencies such as the overproduction observed in April 2024. Conclusively, the implementation of the Least Squares method allows CV. Amirah Ramadhani Cemara to enhance operational efficiency, streamline resource management, and facilitate strategic data-driven decision-making.